2017
DOI: 10.22190/full1602103h
|View full text |Cite
|
Sign up to set email alerts
|

Refusals in the Production of Serbian Esp Learners

Abstract: Abstract. Pragmatics plays a very important role in the process of communication, and the speech act of refusal is performed on a daily basis and in a variety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Blum- Kulka's (1982) claim that language learners often fail to realize their communicative acts in terms of social appropriateness and pragmatic effectiveness generated interest in the strategies employed by EFL/ESL learners. Throughout the growing body of research, the inadequate pragmatic knowledge of the EFL/ESL learners, including ESP learners (Sirikhan & Prapphal 2011;Halupka-Rešetar & Knežević 2016;Taghizadeh 2017;Kreishan 2018), compared to the native speakers' linguistic performance, was reported.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Blum- Kulka's (1982) claim that language learners often fail to realize their communicative acts in terms of social appropriateness and pragmatic effectiveness generated interest in the strategies employed by EFL/ESL learners. Throughout the growing body of research, the inadequate pragmatic knowledge of the EFL/ESL learners, including ESP learners (Sirikhan & Prapphal 2011;Halupka-Rešetar & Knežević 2016;Taghizadeh 2017;Kreishan 2018), compared to the native speakers' linguistic performance, was reported.…”
Section: Previous Researchmentioning
confidence: 99%
“…Research has shown that learners lacked the ability to realize successful speech acts in different social contexts (Halupka-Rešetar & Knežević 2016) and pragmatic failures were noted in both pragmalinguistics and sociolinguistics (Sirikhan & Prapphal 2011). Overall, the studies supported Bardovi-Harlig and Dörnyei's (1998: 234) claim that "grammat ical development does not guarantee a corresponding level of pragmatic development".…”
Section: Previous Researchmentioning
confidence: 99%